Studies on the Glutathione-Dependent Formaldehyde-Activating Enzyme from Paracoccus denitrificans - Hopkinson, Richard J. (Public Library of Science, 2015)

(untitled) (PLoS One)
Formaldehyde is a toxin and carcinogen that is both an environmental pollutant and an endogenous metabolite. Formaldehyde metabolism, which is probably essential for all aerobic cells, likely proceeds via multiple mechanisms, including via a glutathione-dependent pathway that is widely conserved in bacteria, plants and animals. However, it is unclear whether the first step in the glutathione-dependent pathway (i.e. formation of S-hydroxymethylglutathione (HMG)) is enzyme-catalysed. We report studies on glutathione-dependent formaldehyde-activating enzyme (GFA) from Paracoccus denitrificans, which has been proposed to catalyse HMG formation from glutathione and formaldehyde on the basis of studies using NMR exchange spectroscopy (EXSY). Although we were able to replicate the EXSY results, time course experiments unexpectedly imply that GFA does not catalyse HMG formation under standard conditions. However, GFA was observed to bind glutathione using NMR and mass spectrometry. Overall, the results reveal that GFA binds glutathione but does not directly catalyse HMG formation under standard conditions. Thus, it is possible that GFA acts as a glutathione carrier that acts to co-localise glutathione and formaldehyde in a cellular context.